Prevalence and Factors Associated with Anemia in Children Aged 12-24 Months In Darul Imarah Sub-District Aceh Besar District - Suryana; Madanijah, Siti; Sukandar, Dadang (Pakistan Journal of Nutrition, 2016)
This study was aimed to determine the prevalence and factors affecting the anemia status of children aged 12-24 months in Darul Imarah Sub-district, Aceh Besar District. Sample was selected using stratified random sampling technique with proportional allocation. The classification was based on pre-prosperous household/ prosperous I (Jeumpet village = 56 people), prosperous II (Lambheu village = 40 people) and prosperous III (Geugajah village = 45 people) which stood as each layer. Minimum sample size was 102 children aged 12-24 months. Children’s characteristics, socioeconomic status of the family, nutrition and health knowledge of the mothers, feeding practices and history of diarrhea and upper respiratory tract infection (URTI) were measured by using a structured questionnaire. Food consumption was measured through a 24 h recall method. Anthropometric nutritional status was measured by weight-for-age index (WAZ) and length-for-age (LAZ). Hb level was measured by Hemocue 201+ tool. Based on the results of the current study, the anemia prevalence among children aged 12-24 months in Darul Imarah Sub-district, Aceh Besar District was categorized as severe nutrition and public health problem (68.6%). Based on the overall results of regression analysis, the dominant variables affecting anemia status of children were Fe adequacy level (PE = 0.017; R = 0.117), energy adequacy level (PE = -0.013; R = 0.029), length of education of the father (PE = 0.126; R = 0.033), income per capita (PE = -0.657; R = 0.040) and father’s age (PE = -0.020; R = 0.022). Among these five factors, iron adequacy level contributed greatly to the occurrence of anemia in children aged 12-24 months (11.7%). It is thus concluded that high prevalence of anemia in Darul Imarah Sub-district, Aceh Besar District requires special attention from the local government to plan or make policies regarding treatment or prevention program of anemia problem in children under two years, especially in the age group of 12-24 months. There is a need to increase the knowledge and practice about the appropriate child feeding practices, especially the consumption of various plant and animal food sources, as well as iron rich foods.